2004
DOI: 10.1521/ijgp.54.3.295.40340
|View full text |Cite
|
Sign up to set email alerts
|

Group Therapy for Depressed Elderly Women

Abstract: We describe and evaluate a group therapy program targeting depression among elderly residents (N=303) of subsidized high-rise apartments in Nashville, TN. This eclectic program was comprised of 12 sessions (a total of 24 hours) that included modules on exercise and preventive health behaviors, cognitive and re-motivation therapy, reminiscence and grief therapy, and social skills development. Our multivariate regression analyses of pre-post measures using the Geriatric Depression Scale (GDS) showed that the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 23 publications
1
23
1
1
Order By: Relevance
“…Applying this type of intervention is of not only social, but also therapeutic and clinical importance. These results are consistent with those of other studies that likewise observed significant increases in self-esteem (Bohlmeijer et al, 2003;Hsieh & Wang, 2003;Husaini et al, 2004;Pinquart et al, 2007;Wang, 2007) following integrative reminiscence therapy.…”
Section: Discussionsupporting
confidence: 92%
“…Applying this type of intervention is of not only social, but also therapeutic and clinical importance. These results are consistent with those of other studies that likewise observed significant increases in self-esteem (Bohlmeijer et al, 2003;Hsieh & Wang, 2003;Husaini et al, 2004;Pinquart et al, 2007;Wang, 2007) following integrative reminiscence therapy.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, reminiscence therapy is successful in improving one's comprehension skills and in boosting self-esteem, to ease the feeling of depression and hopelessness, and to enhance self-integration. Many studies point out the positive effects of reminiscence therapy and highlight its effectiveness in the easing of depressed feelings (Bohlmeijer et al, 2003;Hsieh and Wang, 2003;Husaini et al, 2004;Wang, 2005;Pinquart et al, 2007), it is also known to be beneficial to an aged persons psychological well-being (Tatchell and Jordan, 2004;McKee et al, 2005;Zauszniewski et al, 2006), it assists to ease feelings of loneliness , and can ameliorate negative emotions and anxiety (Chou et al, 2008). Reminiscence therapy does have a role in the maintenance of self-esteem (Lin et al, 2003;Chao et al, 2006;Nomura and Hashimoto, 2006), self-value (Baker, 1985), better coping skills (Nugent, 1995), increased satisfaction with life (Cook, 1998;Lin et al, 2003), enhanced self-integration (Stinson and Kirk, 2006;Zauszniewski et al, 2006), enhancement of functional activities (Kovach and Henschel, 1996;Woods et al, 2005;Zauszniewski et al, 2006), improved social functions and activities (King, 1982;Cook, 1991), prevention of behavioral problems (Kovach and Henschel, 1996), and in the effective care of the aged person (Shellman, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…An additional two articles were identified(50, 51) that reported depression treatment outcomes for an elderly minority sample as defined by the authors (i.e., age 50+ and age 55+, respectively) with mean age scores over 60 years. Thus, seven studies met inclusion criteria and were included in the final analysis (see Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Studies included data from one or more of the following treatment settings: primary care clinics(4547, 50), social services agencies(49), inpatient settings(48), subsidized housing(51), and home care(47). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation